Cawisan Tradition and The Construction of Religious Moderation - Muslimin, Muslimin; Wibisono, Yusuf (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2022)
This article discusses about religion and social transformation thourgh the Cawisan Tradition in Ogan Ilir, South Sumatra. In this article, religion is seen as part of the cultural system. Indonesia has a variety of traditions and cultures in maintaining religious values, one of the regions that has a disctinctive tradition is the Ogan Ilir Regency of South Sumatra with its Cawisan Tradition. The Existence of Cawisan from the Palembang sultanate era until now has constructed the moderate religious attitude of the community and of course it is interesting to futher study the peculiarities that exist in tradition. So how is the Cawisan tradition for the people of Ogan Ilir South Sumatra? And How is the construction of religious moderation it the Cawisan Tradition? These two questions are discussed by the author thourgh qualitative research methods with descriptive analysis. In answering the above questions, The researcher extracted information by interviewing and participating in Cawisan activities. As well as a conducting a literature review. As a result, It is generally found that the religious moderation is built on the original character of the community and the religious information they receive from local scholars who devote themselves to their respective home villages.